Multicentric phase II trial of TI‐CE high‐dose chemotherapy with therapeutic drug monitoring of carboplatin in patients with relapsed advanced germ cell tumors. (5th March 2021) - Chevreau, Christine; Massard, Christophe; Flechon, Aude; Delva, Rémy; Gravis, Gwenaëlle; Lotz, Jean‐Pierre; Bay, Jacques‐Olivier; Gross‐Goupil, Marine; Fizazi, Karim; Mourey, Loïc; Paci, Angelo; Guitton, Jérôme; et al.
ABSTRACT: Background: High‐dose chemotherapy (HDCT) with TI‐CE regimen is a valid option for the treatment of relapsed advanced germ cell tumors (GCT). We report a phase II trial with therapeutic drug monitoring of carboplatin for optimizing area under the curve (AUC) of this drug. Methods: Patients with unfavorable relapsed GCT were treated according to TI‐CE regimen: two cycles combining paclitaxel and ifosfamide followed by three cycles of HD carboplatin plus etoposide administered on 3 days. Carboplatin dose was adapted on day 3 based on carboplatin clearance (CL) at day 1 in order to reach a target AUC of 24 mg.min/mL per cycle. The primary endpoint was the complete response (CR) rate. Results: Eighty‐nine patients who received HDCT were included in the modified intent‐to‐treat (mITT) analysis. Measured mean AUC was 24.4 mg.min/mL per cycle (22.4 and 26.8 mg.min/mL for 10th and 90th percentiles). Thirty‐five (44.3%) patients achieved a CR with or without surgery of residual masses and 20 patients achieved a partial response with negative tumor markers. With a median follow‐up of 44 months (m), median PFS was 12.3 m (95% CI: 7.5–25.9) and OS was 46.3 m (95% CI: 18.6–not reached). For high‐ and very high‐risk patients, according to the International Prognostic Score at first relapse or treated after at least one salvage treatment (n = 51), 2‐year PFS rate was 41.1%. Conclusion: The rates of complete and favorable responses were clinically relevant in this very poor risk population. Individual monitoring of carboplatin plasma concentration permitted to control more accurately the target AUC and avoided both underexposure and overexposure to the drug. Abstract : The superiority of HDCT over standard chemotherapy as initial salvage treatment of patients with relapsed or refractory germ cell tumors remains a valid question. In the TI‐CE regimen, TDM was demonstrated to be feasible in routine practice and really allowed to control target AUC more accurately compared to previous reports, avoiding both underexposure and overexposure to carboplatin. In our study, the rate of CR observed in this population with very poor prognosis was 44.3% and increased to 69.6% of favorable responses. Based on our study and if the benefit of HDCT is proven in the TIGER trial, we suggest that the use of carboplatin TDM for dose individualization in current practice should be considered.